Challenging obduracy: How local communities transform the energy system - Schoor, Tineke van der; Lente, Harro van; Scholtens, Bert; Peine, Alexander (Energy research & social science, 2016)
•New energy movement challenges present governance of energy system.•Sustainability and strengthening regional economy are primary goals.•Democratic cooperative model should safeguard citizen influence.•Grassroots innovation of energy system brought about by networks of motivated citizens. The transformation from the current energy system to a decentralized renewable energy system requires the transformation of communities into energy neutral or even energy producing communities. Increasingly, citizens become ‘prosumers’ and pool their resources to start a local energy initiative. In this paper we present an in-depth study of networks that recently developed, which challenge the established way of centralized decision-making on energy resources. Many local communities are eager to promote sustainable energy production, to use local financial resources for the local community and to employ democratic governance of energy production and supply. Furthermore, we study how these co-operations are linked to local, regional and national networks for community energy. We use both Actor-Network Theory (ANT) and Social Movement Theory (SMT) to investigate the initiatives, as this allows a dynamic analysis of collective strategies. We discuss the obduracy of the energy system and how this system is challenged by new connections between communities and global networks and by new types of energy providers that are rooted in social networks. Furthermore, we draw attention to the way community energy networks provide a social innovation while realizing a decentralized and decarbonized energy system.